Development of a Natural Science Module Based on Local Tourism, Wonosobo Color Lake, to Improve Mastery of Concepts for Junior High School Students on Light and Optical Instruments - Fatimah, Anik Zuhriatul; Maryono, Maryono; Firdaus, Firdaus (Department of Physics Education, Universitas Mataram, 2023)
This study aims to develop valid and practical physics modules to be used in teaching physics in class. The module developed is a module that is integrated with local tourism of the colorful lakes in Wonosobo, with the material described in the module being light material and optical devices. In addition, the developed module also aims to improve students' mastery of concepts. In this study using Research and Development (R&D), namely research methods that produce products in the form of modules, media and others. Data collection techniques used in this study were observation, questionnaires, tests and documentation. The instruments used in data collection were media expert validation sheets, material experts, student response questionnaires, and student concept mastery test questions. The subjects of this study were 17 students of grade VIII junior high school. From the research that has been done, the results are (1) module validation by media experts, material experts, and practitioner experts, an overall percentage of 80.1% is included in the valid category; (2) the results of the practicality of the modules assessed by students obtained an overall percentage of 87.82% including the very practical category; (3) being able to improve students' mastery of concepts based on the results of the average pretest and posttest scores, there was an increase in scores, the pretest obtained an average score -an average of 52.05, while the posttest obtained an average of 88.52.